Telomere dynamics and oxidative stress in Arabidopsis grown in lunar regolith simulant - Barcenilla, Borja Barbero; Kundel, Ishan; Hall, Emily; Hilty, Nicolas; Ulianich, Pavel; Cook, Jillian; Turley, Jake; Yerram, Monisha; Min, Ji-Hee; Castillo-González, Claudia; Shippen, Dorothy E. (Frontiers in Plant Science, 2024)
NASA envisions a future where humans establish a thriving colony on the Moon by 2050. Plants will be essential for this endeavor, but little is known about their adaptation to extraterrestrial bodies. The capacity to grow plants in lunar regolith would represent a major step towards this goal by minimizing the reliance on resources transported from Earth. Recent studies reveal that Arabidopsis thaliana can germinate and grow on genuine lunar regolith as well as on lunar regolith simulant. However, plants arrest in vegetative development and activate a variety of stress response pathways, most notably the oxidative stress response. Telomeres are hotspots for oxidative damage in the genome and a marker of fitness in many organisms. Here we examine A. thaliana growth on a lunar regolith simulant and the impact of this resource on plant physiology and on telomere dynamics, telomerase enzyme activity and genome oxidation. We report that plants successfully set seed and generate a viable second plant generation if the lunar regolith simulant is pre-washed with an antioxidant cocktail. However, plants sustain a higher degree of genome oxidation and decreased biomass relative to conventional Earth soil cultivation. Moreover, telomerase activity substantially declines and telomeres shorten in plants grown in lunar regolith simulant, implying that genome integrity may not be sustainable over the long-term. Overcoming these challenges will be an important goal in ensuring success on the lunar frontier.